Short Communication: Genetic diversity of scalloped hammerhead sharks (Sphyrna lewini) landed in Muncar Fishing Port, Banyuwangi (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Alghozali FA, Wijayanti DP, Sabdono A. 2019. Short Communication: Genetic diversity of scalloped hammerhead sharks (Sphyrna lewini) landed in Muncar Fishing Port, Banyuwangi. Biodiversitas 20: 1154-1159. The majority of sharks caught in Indonesian fisheries were bycatch products from the tuna longline fisheries, but some regions in Indonesia fish the sharks as their main target. One of these regions is located in Muncar, Banyuwangi, which fishes the endangered Scalloped Hammerhead sharks (Sphyrna lewini) as target species. This research aimed to study the genetic diversity of the endangered Scalloped Hammerhead sharks landed in Muncar Fishing Port, Banyuwangi. Genetic analysis was done through PCR (Polymerase Chain Reaction) amplification and sequencing of the mitochondrial DNA COI (Cytochrome Oxidase subunit I) gene. Out of the 37 samples collected, 30 were successfully amplified and sequenced.The results showed moderate haplotype diversity (Hd: 0,582 ± 0,079) and low nucleotide diversity (?: 0,00392± 0,0024) with five haplotypes (h) and 26 polymorphic sites (S). Tajima’s D neutrality model values indicated a population expansion event. Two different clades were determined through phylogenetic analysis and by GenBank sequences comparison. These results provided basic information and present status of the Scalloped Hammerhead sharks population genetically within the fishing ground (Makassar Strait-Kangean Islands).